A modified homotopy perturbation method for purely nonlinear fin-type problems - Chowdhury, Md. Sazzad Hossien; Hashim, Ishak (Pushpa Publishing House, 2007)
In this paper, a modifcation of the homotopy-perturbation method (HPM) is pre-sented to determine the temperature distribution of a straight rectangular fin with power-law temperature dependent surface heat flux. The dimensionless nonlinear boundary-value problem is solved analytically by the modified homotopy-pertur-bation method (MHPM). Comparisons of the results obtained by MHPM with that obtained by the Adomian decomposition method (ADM) and the available exact solutions suggest that the MHPM with its simplicity can be a useful tool for many engineering applications.